Digital Storytelling, Cultural Identity, and Audience Persuasion in Sustainable Tourism: A Systematic Literature Review of Dual-Route Elaboration Mechanisms - Lalu Muhammad Rifqi Nugraha; Maulina Pia Wulandari; Zulkarnain (Lembaga Bale Literasi, 2026)
This systematic literature review maps the intersection of digital storytelling, cultural identity, and the Elaboration Likelihood Model (ELM) in sustainable tourism communication. ELM has been consistently applied in digital tourism research to explain how destination content shapes tourist attitudes, yet its application to institutional credibility as a governance outcome remains largely unexplored. Following PRISMA 2020 guidelines and guided by a PICO framework, systematic searches of Scopus yielded 25 studies after screening and full-text review. Thematic synthesis identified five clusters: ELM dual-route persuasion in tourism digital communication; digital storytelling and cultural destination perception; cultural identity, indigenous tourism, and peripheral cues; organizational reputation and institutional credibility; and community engagement and social media governance. Key findings indicate that peripheral-route cues, particularly source credibility and cultural-aesthetic stimuli, exert stronger effects on immediate behavioral intention than central-route argument quality. Cultural identity functions as a multi-level peripheral cue and, when grounded in authenticity and ecological knowledge, also activates central route elaboration. Critically, institutional credibility as a governance outcome is addressed explicitly in only four of 25 included studies. This review proposes a dual-route governance signalling framework positioning institutional credibility not destination image as the primary governance outcome of government-managed cultural tourism storytelling.